2019
DOI: 10.1093/nar/gkz720
|View full text |Cite
|
Sign up to set email alerts
|

Structure and DNA damage-dependent derepression mechanism for the XRE family member DG-DdrO

Abstract: DdrO is an XRE family transcription repressor that, in coordination with the metalloprotease PprI, is critical in the DNA damage response of Deinococcus species. Here, we report the crystal structure of Deinococcus geothermalis DdrO. Biochemical and structural studies revealed the conserved recognizing α-helix and extended dimeric interaction of the DdrO protein, which are essential for promoter DNA binding. Two conserved oppositely charged residues in the HTH motif of XRE family proteins form salt bridge inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Surprisingly, DdrO dimerization via its CTD was not considered and investigated in Lu et al. (42), although the same CTD-CTD interfaces and DdrO polymer as found for D. deserti DdrO are present in their crystal structure (PDB code 6JQ1). Our work includes a domain dissection approach and a number of in vitro , in vivo and in silico experimental data that support the model that DdrO dimerization is mediated by its CTD and that cleavage by IrrE prevents this dimerization mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, DdrO dimerization via its CTD was not considered and investigated in Lu et al. (42), although the same CTD-CTD interfaces and DdrO polymer as found for D. deserti DdrO are present in their crystal structure (PDB code 6JQ1). Our work includes a domain dissection approach and a number of in vitro , in vivo and in silico experimental data that support the model that DdrO dimerization is mediated by its CTD and that cleavage by IrrE prevents this dimerization mode.…”
Section: Discussionmentioning
confidence: 99%
“…After this work was submitted and the referees’ reports received, an article reporting a crystal structure of full-length DdrO from Deinococcus geothermalis was published by Lu et al. (42). Their structure is essentially identical to the full-length D. deserti DdrO structure presented here, also with the NTD dimer contained in the asymmetric unit (as in Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…1 H) [20] and D. deserti [19] have been determined recently and are essentially identical. Structural analysis revealed that DdrO has an HTH-containing N-terminal domain with a pair of oppositely charged residues (RE pair) for substrate binding, which is conserved within XRE family proteins [20] . An additional C-terminal domain with a novel fold is connected by a 15 amino acid linker loop.…”
Section: Proteins In Effective Dna Repair Processesmentioning
confidence: 70%
“…In addition, a common DNA motif called RDRM (radiation/desiccation response motif) was identified in a set of promoter regions of DNA repair genes (e.g., recA , pprA ) [18] . It was recently revealed that DdrO, a self-regulated repressor specifically binding to the RDRM, tightly controls the expression of these genes under normal growth conditions [19] , [20] , [21] , [22] . The transcription of these genes is stimulated by the metalloprotease PprI, also referred to as IrrE.…”
Section: Introductionmentioning
confidence: 99%
“…As reported before, pprI from D. deserti shares 73 and 64% sequence identity with D. geothermalis and D. radiodurans homologs and can complement the loss of radiation resistance of pprI deletion in D. radiodurans ( Vujicic-Zagar et al, 2009 ). It is also demonstrated that PprI from either D. geothermalis or D. radiodurans can cleave DdrO from either D. geothermalis or D. radiodurans , further demonstrating that PprI cleavage of DdrO as well as the PprI–DdrO response system is conserved among Deinococcus species ( Lu et al, 2019 ).…”
Section: Ppri Structure Reveals Three Distinct Domainsmentioning
confidence: 97%